MEMBANGUN KOMUNIKASI KELUARGA PADA PASANGAN NIKAH MUDA SEBAGAI BENTENG KETAHANAN KELUARGA - Muhammad Nabih Ali; M. Marovida Aziz (TAQNIN: Jurnal Syariah dan Hukum, 2022)
This paper aims to show that through the development of good communication will give birth to a good relationship, as well as in creating family resilience in young married couples. The method used in this paper is descriptive analytical. While this research by looking for data in the form of interviews with young married couples. As a result, several concepts are offered to create family resilience, namely mutual openness, mutual understanding, and mutual care, as well as aspects of trust, commitment, and sympathy and empathy. Communication is an important element that must exist in a relationship, including in married life. Weak communication in the family will cause divisions, disputes, and conflicts that can lead to divorce. Communication that is built well between family members will create a harmonious family, so as to avoid disputes and fights. Keywords: communication, family, family resilience, young marriage.